Exploring the Interplay of Investment Knowledge, Motivation, Minimum Capital, and Risk Perception in Shaping Students' Interest in Capital Markets - Hasanudin Hasanudin (Jurnal Manajemen dan Kewirausahaan, 2023)
The primary objective of this research is to conduct an analysis of the impact of independent variables, specifically Investment Knowledge, Motivation, Minimum Capital, and Risk Perception, on Investment Interest. The study encompasses the 2019 cohort of students enrolled in the Management Study Program, comprising a total of 453 individuals, including both regular students and employees. The selection of the research sample follows a probabilistic approach, utilizing purposive sampling techniques. This method involves the establishment of specific criteria that prospective samples must meet, resulting in a final sample size of 212 students. Data collection was accomplished through the distribution of questionnaires to the student cohort, serving as the primary data collection instrument. The data analysis procedures employed in this study encompass descriptive analysis and inferential analysis, with the latter involving multiple linear regression. Statistical analysis was conducted using the Statistical Product and Service Solution (SPSS) version 23.0 software. The findings of this research underscore the significant and positive influence of Motivation, Minimum Capital, and Risk Perception on Investment Interest. However, it is worth noting that Investment Knowledge, while positively correlated with Investment Interest, did not yield statistically significant results in this context.